Las clases sociales en polvo y ceniza de Eliécer Cárdenas Espinosa - Gaona Cumbicus, Doris Karina (2015)
This paper entitled Social classes in dust and ashes of Eliécer Cárdenas Espinosa, was proposed as general objective to describe the social classes that are evident in the work of dust and ashes, and its influence on the characters and perform a comparative study existing social classes in our current capitalist society and that the author focuses on the work under consideration. The methodology was guided by the methods: analytical - synthetic, inductive - deductive scientist and a specific method for literary analysis, critical Ephraim Subero based method was used, resulting in pre-existing social classes at that time were the landlords because in Loja sent three families: Eguiguren, Burneo Valdivieso and "concluded that there was a social chiefdom that had powers to influence in its favor in Loja, leading to recommend teachers of language and literature proposing texts that permit, to know the influence that inspires the narrative of Cardenas, ie, broaden the knowledge of the historical-present reality Ecuador and understand historical and social contexts of the time.